Meraih Potensi Anak dengan Etnoparenting: Sosialisasi Parenting di TK Islam Qonita - Ade Veni Yunianti; Eva Indrianti; Endang Siregar; Pratika Rindriani; Kaila Murni; Eka Amelia; Winda Sherly Utami; Indriyani (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Early childhood education plays an important role in building the foundation of a child's character and potential. Ethnoparenting, which combines cultural values, is an effective approach to achieving this goal. This socialization aims to increase parents' understanding of the concept of ethnoparenting and its application in educating young children. Through this activity, it is hoped that parents can understand local cultural values that can be integrated into the childcare process, as well as improve the quality of childcare at TK Islam Qonita. This socialization was carried out through several stages, namely the preparation stage, implementation stage and evaluation stage. The results of the ethnoparenting socialization activities at the TK Islam Qonita have succeeded in increasing parents' understanding of the concept of ethnoparenting and its application in educating young children. This activity also succeeded in improving the quality of care at TK Islam Qonita through the integration of local cultural values in the learning and care process for children.